Low-modulus ion-exchangeable glass

KR103013590B1Active Publication Date: 2026-09-02CORNING INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020227023080
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-12
Filing Date
2020-12-11
Publication Date
2026-09-02
Estimated Expiration
2040-12-11

Smart Images

  • Figure 112022070068919-PCT00011_ABST
    Figure 112022070068919-PCT00011_ABST
Patent Text Reader

Abstract

An ion-exchanged alkali aluminosilicate glass article is disclosed having a ratio of the peak compressive stress value to the Young's modulus value of 14 or greater. The glass article may comprise Al2O3 mol% + RO mol% ≥ 18 mol%, wherein RO mol% = MgO mol% + CaO mol%, and substantially does not contain ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O. The glass article may have a peak compressive stress value in the range of 850 MPa to 1400 MPa. The glass article is suitable for various high-strength applications, including cover glass applications that experience significant bending stress during use, e.g., cover glass for flexible displays.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] This application claims priority to U.S. Provisional Application No. 62 / 947817 filed on December 13, 2019 and NL 2024883 filed on February 12, 2020.

[0002] This description relates to ion-exchangeable glass compositions. Specifically, the embodiments described herein relate to ion-exchangeable glass compositions for use in various industries, e.g., consumer electronics, transportation, construction, defense, medical, and packaging. More specifically, this description relates to glass compositions for cover glass applications, e.g., cover glass for flexible displays. Background Technology

[0003] Many consumer products, such as smartphones, tablets, portable media players, personal computers, and cameras, include cover glass that can function as a display cover and may include touch functionality. Often, if these devices are dropped by a user onto a hard surface, the cover glass can be damaged, which can negatively affect the use of the device (e.g., the touch function may be impaired).

[0004] Foldable or flexible displays for consumer electronics applications can benefit from thin, flexible ion-exchange glass. The glass can increase its resistance to flexure failure through an ion-exchange process that induces compressive stress on the glass surface. The compressive stress introduced using the ion-exchange process serves, among other things, to prevent defects that could cause glass breakage. The problem to be solved

[0005] Therefore, there is a continuing demand for ion-exchangeable glass compositions having desirable mechanical properties for use in various applications, including cover glass applications. means of solving the problem

[0006] This specification relates to an ion-exchangeable glass composition having strength and flexibility suitable for various applications, e.g., for cover glass applications for electronic devices. The glass composition disclosed herein has a value of 18 mol% or more (Al2O3 mol% + RO mol%). The glass composition is designed to maximize the ratio of the peak compressive stress value to the Young's modulus value. A high ratio, e.g. 14 or more, enables the glass composition to resist fracture during bending events. Furthermore, the strength imparted to the glass composition by the ion exchange process provides the glass composition with desirable mechanical properties that resist fracture during use.

[0007] The first aspect (1) of the present application relates to an ion-exchanged alkali aluminosilicate glass article, said glass article comprising SiO2, 13.5 mol% or more of Al2O3, 1 mol% to 5 mol% of MgO, CaO, Na2O, wherein: Al2O3 mol% + RO mol% ≥ 18 mol%, RO mol% = MgO mol% + CaO mol%, said glass article substantially free of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O. said glass article also has a Young's modulus value measured in GPa before ion exchange and a compressive stress layer extending from the surface of the glass article to a compressive depth, said compressive stress layer having a peak compressive stress value measured in MPa, wherein the ratio of the peak compressive stress value to the Young's modulus value is 14 or more.

[0008] In the second aspect (2), a glass article according to the first aspect (1) is provided, and Al2O3 mol% + RO mol% ≥ 20 mol%.

[0009] In the third aspect (3), a glass article according to either the first aspect (1) or the second aspect (2) is provided (Na2O mol% + RO mol% - Al2O3 mol%) ≥ 0 mol %.

[0010] In the fourth aspect (4), a glass article according to any one of aspects (1) - (3) is provided, and 7 mol% ≥ (Na2O mol% + RO mol% - Al2O3 mol%) ≥ 0 mol%.

[0011] In the fifth aspect (5), a glass article according to any one of aspects (1) - (4) is provided, and said glass article has a liquidus viscosity in the range of 50 kP to 500 kP measured before ion exchange.

[0012] In the sixth aspect (6), a glass article according to any one of aspects (1) to (5) is provided, and said glass article comprises 0.5 mol% to 2 mol% CaO, and Al2O3 mol% + RO mol% ≥ 20 mol%.

[0013] In the seventh aspect (7), a glass article according to any one of aspects (1) to (6) is provided, and the ratio of the peak compressive stress value to the Young's modulus value is 15 or more and 18 or less.

[0014] In the eighth aspect (8), a glass article according to any one of aspects (1) to (7) is provided, and the Young's modulus value is in the range of 70 MPa to 80 MPa.

[0015] In the ninth aspect (9), a glass article according to any one of aspects (1) to (8) is provided, and the peak compressive stress is in the range of 850 MPa to 1400 MPa.

[0016] In the 10th aspect (10), a glass article according to any one of aspects (1) to (9) is provided, and the compression depth is in the range of 5 microns to 40 microns.

[0017] In the 11th aspect (11), a glass article according to any one of aspects (1) - (9) is provided, and the compression depth is in the range of 5 microns to 20 microns.

[0018] In the 12th aspect (12), a glass article according to any one of aspects (1) - (11) is provided, and the compression depth is in the range of 5% to 20% of the thickness of the glass article.

[0019] In the 13th aspect (13), a glass article according to any one of aspects (1) - (12) is provided, and the peak compressive stress is in the range of 1100 MPa to 1350 MPa and the compressive depth is in the range of 5 microns to 20 microns.

[0020] In the 14th aspect (14), a glass article according to any one of aspects (1) to (13) is provided, and the glass article comprises 59 mol% to 66 mol% SiO2, 13.5 mol% to 20 mol% Al2O3, 0.5 mol% to 2 mol% CaO, and 15 mol% to 18 mol% Na2O.

[0021] In the 15th aspect (15), a glass article according to any one of aspects (1)-(13) is provided, and said glass article comprises 60 mol% to 65 mol% SiO2, 16 mol% to 18 mol% Al2O3, 2 mol% to 4 mol% MgO, 0.5 mol% to 2 mol% CaO and 15 mol% to 18 mol% Na2O.

[0022] In the 16th aspect (16), a glass article according to the 15th aspect (15) is provided, and Al2O3 mol% + RO mol% ≥ 20 mol%.

[0023] In the 17th aspect (17), a glass article according to any one of aspects (1) to (13) is provided, and the glass article contains 16 mol% or more of Al2O3.

[0024] In the 18th aspect (18), a glass article according to any one of aspects (1) to (17) is provided, and 23 mol% ≥ Al2O3 mol% + RO mol% ≥ 18 mol%.

[0025] In the 19th aspect (19), a glass article according to any one of aspects (1) - (18) is provided, and (MgO mol% / (MgO mol% + CaO mol%)) ≥ 0.5.

[0026] In the 20th aspect (20), a glass article according to any one of aspects (1) to (18) is provided, and (MgO mol% / (MgO mol% + CaO mol%)) ≥ 0.55.

[0027] In the 21st aspect (21), a glass article according to any one of aspects (1) to (20) is provided, and the glass article has a thickness of 4 millimeters or less.

[0028] In the 22nd aspect (22), a glass article according to any one of aspects (1) to (20) is provided, and the glass article has a thickness in the range of 15 microns to 200 microns.

[0029] The 23rd aspect (23) of the present application relates to an electronic device comprising an electronic display and a glass article according to any one of aspects (1) to (22) disposed on the electronic display.

[0030] In the 24th aspect (24), an electronic device according to the 23rd aspect (23) is provided, and the electronic device comprises a housing including a front, a rear and a side; and at least partially an electrical component within the housing, wherein the electrical component comprises a controller, a memory and an electronic display, and the electronic display is located on or adjacent to the front of the housing, and the glass article forms at least a part of the housing.

[0031] The 25th aspect (25) of the present application relates to an ion-exchanged glass article comprising 59 mol% to 66 mol% SiO2, 13.5 mol% to 20 mol% Al2O3, 1 mol% to 5 mol% MgO, 0.5 mol% to 2 mol% CaO, 15 mol% to 18 mol% Na2O, a Young's modulus value measured in GPa units of the ion-exchanged glass article, and a compressive stress layer extending from the surface of the ion-exchanged glass article and having a peak compressive stress value measured in MPa, wherein: Al2O3 mol% + RO mol% ≥ 18 mol%, RO mol% = MgO mol% + CaO mol%, the glass article is substantially free of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O, and the ratio of the peak compressive stress value to the Young's modulus value is 14 or greater and 18 or less.

[0032] In aspect 26 (26), a glass article according to aspect 25 (25) is provided, and the glass article comprises 60 mol% to 65 mol% SiO2, 16 mol% to 18 mol% Al2O3, 2 mol% to 4 mol% MgO, 0.5 mol% to 2 mol% CaO, and 15 mol% to 18 mol% Na2O.

[0033] In the 27th aspect (27), a glass article according to the 25th aspect (25) or the 26th aspect (26) is provided, and the glass article has a thickness ranging from 20 microns to 200 microns.

[0034] The 28th aspect (28) of the present application relates to a method for strengthening a glass article, the method comprising: immersing a glass article in an ion exchange solution containing 50 weight% or more of a potassium salt, wherein the glass article comprises: SiO2, 13.5 mol% or more of Al2O3, 1 mol% to 5 mol% of MgO, CaO, and Na2O, wherein: Al2O3 mol% + RO mol% ≥ 18 mol%, RO mol% = MgO mol% + CaO mol%, and the glass article is substantially free of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O; and ion-exchanging the glass article in the ion exchange solution for a period of 1 hour to 24 hours at a temperature in the range of 350°C to 480°C to achieve a compressive stress layer extending from the surface of the glass article to a compressive depth and comprising a peak compressive stress value in the range of 850 MPa to 1400 MPa.

[0035] In the 29th aspect (29), a method according to the 28th aspect (28) is provided, and the compression depth is in the range of 5 microns to 40 microns.

[0036] In the 30th aspect (30), a method according to the 28th aspect (28) is provided, and the compression depth is in the range of 5 microns to 20 microns.

[0037] In the 31st aspect (31), a method according to any one of aspects (28) to (30) is provided, and the peak compressive stress value is in the range of 1100 MPa to 1350 MPa and the compressive depth is in the range of 5 microns to 20 microns.

[0038] In the 32nd view (32), a method according to any one of views (28) to (31) is provided, and the duration is in the range of 1 hour to 8 hours.

[0039] In aspect 33 (33), a method according to any one of aspects (28) to (32) is provided, and the glass article has a liquidus viscosity in the range of 50 kP to 500 kP measured before being immersed in an ion exchange solution.

[0040] In the 34th aspect (34), a method according to any one of aspects (28) to (33) is provided, and the glass article has a Young's modulus value measured in GPa before being immersed in an ion exchange solution, and the ratio of the peak compressive stress value to the Young's modulus value is 14 or more and 18 or less.

[0041] In the 35th aspect (35), a method according to the 34th aspect (34) is provided, and the ratio of the peak compressive stress value to the Young's modulus value is 15 or more and 18 or less.

[0042] In aspect 36 (36), a method according to any one of aspects (28) to (35) is provided, and the glass article comprises 59 mol% to 66 mol% SiO2, 13.5 mol% to 20 mol Al2O3, 0.5 mol% to 2 mol% CaO, and 15 mol% to 18 mol% Na2O.

[0043] In aspect 37 (37), a method according to any one of aspects (28) to (35) is provided, and the glass article comprises 60 mol% to 65 mol% SiO2, 16 mol% to 18 mol% Al2O3, 2 mol% to 4 mol% MgO, 0.5 mol% to 2 mol% CaO, and 15 mol% to 18 mol% Na2O.

[0044] In the 38th aspect (38), a method according to any one of aspects (28) to (37) is provided, and 23 mol% ≥ Al2O3 mol% + RO mol% ≥ 18 mol%.

[0045] In the 39th aspect (39), a method according to any one of aspects (28) to (38) is provided, and the glass article has a thickness of 4 millimeters or less.

[0046] In the 40th aspect (40), a method according to any one of aspects (28) to (38) is provided, and the glass article has a thickness in the range of 15 microns to 200 microns. Brief explanation of the drawing

[0047] The attached drawings included herein form part of the specification and illustrate embodiments of the described herein. Together with the description, the drawings serve to explain the principles and enable those skilled in the art to create and use the described embodiments. These figures are for illustrative purposes only and are not limiting. While the described herein is generally described in the context of such embodiments, it should be understood that the scope of the described herein is not intended to be limited to these specific embodiments. Identical reference numerals in the drawings indicate identical or functionally similar elements. FIG. 1 illustrates a cross-section of a glass article having a compressive stress region according to some embodiment. FIG. 2 illustrates a cross-sectional view of a glass article according to some embodiments when the glass article is bent. FIG. 3a is a plan view of an exemplary electronic device comprising a glass article according to any glass article disclosed herein. FIG. 3b is a perspective view of the exemplary electronic device of FIG. 3a. Figure 4 is a graph of the depth of a layer versus compressive stress for various exemplary glass compositions. Figure 5 is a graph modeling the stress applied to a glass article during bending at various depths from the surface of the glass article. Figure 6 is a graph modeling the safe plate spacing for a bending test as a function of glass thickness for various exemplary glass compositions. Specific details for implementing the invention

[0048] The following embodiments are exemplary but are not intended to limit the description. Various other appropriate modifications and variations of conditions and parameters commonly encountered in the field and obvious to those skilled in the art are within the spirit and scope of the description.

[0049] The glass described herein is a family of ion-exchangeable alkali aluminosilicate glasses capable of ion-exchangeable to achieve high peak compressive stress. As used herein, "ion-exchangeable" means that a glass composition, or a glass article comprising the composition, can exchange a first cation located on or near the surface of a substrate for a second cation of the same valence. The first ion may be a sodium ion. The second ion may be one of potassium, rubidium, and cesium ions, provided that the second ion has an ionic radius greater than that of the first ion. The first ion exists as an oxide (e.g., Na2O) of the glass-based substrate. As used herein, "ion-exchanged glass" or "chemically strengthened glass" means that at least one ion exchange process has been applied to the glass to exchange a cation located on or near the glass surface for a cation of the same valence.

[0050] The glass compositions described herein may be ion-exchanged to achieve high peak compressive stress. In some embodiments, the glass described herein may be ion-exchanged to achieve peak compressive stresses of about 1000 MPa or more and about 1400 MPa or less. The high peak compressive stress imparted during the ion-exchange process can provide high strength to the glass with a shallow flaw size distribution, thereby preventing breakage during bending. The high peak compressive stress causes the glass to maintain net compression, which includes surface defects when the glass is bent around a narrow radius. The glass according to the embodiments described herein has a low Young's modulus, which results in lower bending stress values ​​during bending and thus can prevent breakage during the bending event.

[0051] Furthermore, the glass compositions described herein have a ratio of peak compressive stress values ​​to Young's modulus values ​​of 14 or higher (peak compressive stress value / Young's modulus value, CS / E, where CS is MPa and E is GPa) over a wide range of compression depths for the compression region created by the ion exchange process. Increasing this ratio is difficult because the surface compressive stress imparted during the ion exchange process can strongly influence Young's modulus, as a higher Young's modulus is a general pathway for improving compressive stress. In other words, Young's modulus is a measure of the stiffness of the network. For example: exchanging K+ ions to Na+ sites generates compressive stress, but as the network becomes stiffer (e.g., as Young's modulus increases), the expansion stress increases. Therefore, one general method to obtain a higher CS is to increase Young's modulus, but what is done in this description is to increase CS without significantly increasing Young's modulus. A high CS / E ratio allows the glass composition to remain flexible even after ion exchange. The glass compositions described herein have a sufficiently low Young's modulus prior to ion exchange and a compressive stress value that can be imparted during the ion exchange process that is sufficiently high to achieve a high CS / E ratio over a wide range of compression depths. As a result, a glass composition is produced that is flexible and accommodates high surface compressive stress values. Because the glass composition resists stress relaxation that may occur during the ion exchange process, it can accommodate high surface compressive stresses at large compression depths, such as, for example, as high as 50 micrometers (microns and / or μm). Stress relaxation may become more pronounced as temperature and time increase, and is prone to occur during ion exchange processes designed to impart high compression depths. These characteristics of the glass compositions described herein make them suitable for various industrial applications, including high-strength cover glass applications that experience significant bending stress when used as cover glass in flexible and foldable displays, for example.

[0052] As used herein, "peak compressive stress" refers to the highest compressive stress (CS) value measured within the compressive stress region. In some embodiments, the peak compressive stress is located on the surface of the glass. In other embodiments, the peak compressive stress occurs at a depth below the surface, which may provide the appearance of a "buried peak" in the compressive stress profile. Unless otherwise specified, compressive stress (including the surface CS) is measured by a surface stress meter (FSM) using a commercially available instrument, for example, the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). The measurement of surface stress depends on the accurate measurement of the stress-optical modulus (SOC) associated with the birefringence of the glass. The SOC is, in turn, measured according to Procedure C (glass disk method) described in ASTM Standard C770-16, titled "Standard Test Method for Measuring the Stress-Optical Modulus of Glass."

[0053] As used herein, "Depth of Compression" (DOC) refers to the depth at which stress within a glass article changes from compression to tension. At the DOC, the stress crosses from compressive stress to tensile stress, so the stress value is zero. The depth of compression and the depth of layer can be measured using a surface stress meter, for example, the FSM-6000 surface stress meter. As used herein, "Depth of Layer" (DOL) refers to the depth within a glass article at which ions of a metal oxide diffuse into the glass article where the ion concentration reaches a minimum value. In an embodiment where only potassium is ion-exchanged into the glass article, the DOC may be the same as the DOL. Unless otherwise specified herein, the DOC and the DOL are the same.

[0054] The glass compositions described herein can also be manufactured at a reasonable cost. The glass compositions exhibit a high liquidus temperature and a suitably low liquidus viscosity for certain manufacturing techniques, e.g., slot drawing. These thermal properties can increase the ease of manufacturing glass articles produced from the compositions, which can reduce costs. The glass compositions described herein have, among other things, values ​​for aluminum oxide content, magnesium oxide content, and Na2O mol% + RO mol% ≥ Al2O3 mol% which aids in melting during manufacturing. In some embodiments, the glass compositions may have a liquidus viscosity in the range of 50 kP (kiloPoise) to 500 kP.

[0055] The glass compositions described herein may provide one or more of the following advantages: (1) The compositions are lithium-free but can achieve high compressive stress values ​​(e.g., up to 1400 MPa) during ion exchange at a small depth of layer (DOL) and up to about 1250 MPa even at a higher DOL of about 40 microns (micrometers, μm). (2) The compositions have a low modulus that facilitates a higher CS / E ratio and improves bendability for thin foldable applications. (3) The raw materials for making the glass are inexpensive and readily available. (4) The compositions are easy to melt due to their high modified sugar content. The "modified sugar" content for the glass compositions means that the value (R2O mol% + RO mol% - Al2O3 mol%) is greater than 0 mol%, where R2O mol% is the total mol% of all alkali metal oxides. Here, RO mol% is the total mol% of all alkaline earth metal oxides in the composition. (5) The composition has a low liquidus temperature, high liquidus viscosity, and a slow-growing liquidus phase, all of which are advantageous for sheet formation.

[0056] As used herein, the term “glass” means any material made at least partially of glass, including glass and glass-ceramics. “Glass-ceramics” include materials produced through the controlled crystallization of glass. One or more nucleating agents, e.g., titanium oxide (TiO2), zirconium oxide (ZrO2), sodium oxide (Na2O), and phosphorus oxide (P2O5), may be added to the glass-ceramic composition to promote uniform crystallization.

[0057] For the glass compositions described herein, the concentrations of constituent components (e.g., SiO2, Al2O3, Na2O, etc.) are provided in mol% (mol%) based on oxides unless otherwise specified. The components of the glass compositions according to embodiments are discussed individually below. It should be understood that any range cited for any component may be individually combined with any range cited for any other component. As used herein, trailing zeros in numbers are intended to indicate significant digits for the corresponding number. For example, the number "1.0" contains two significant digits, and the number "1.00" contains three significant digits. As used herein, a composition described as containing oxides within a range defined as 0 mol% as a lower limit means that the composition contains oxides in amounts greater than 0 mol% (e.g., 0.01 mol% or 0.1 mol%) and up to the upper limit of said range.

[0058] SiO2 can be the largest component in a glass composition and is itself a major component of the glass network formed from the glass composition. Pure SiO2 has a relatively low coefficient of thermal expansion (CTE - this property used here is measured at temperatures from 0°C to 300°C) and is alkali-free. However, pure SiO2 has a high melting point. Therefore, if the concentration of SiO2 in the glass composition is too high, the difficulty of melting the glass increases as the concentration of SiO2 increases, which can reduce the formability of the glass composition, and this, in turn, has a negative effect on the formability of the glass.

[0059] In some embodiments, the glass composition may contain SiO2 in an amount of 55 mol% or more to 70 mol% or less, and in all ranges and sub-ranges between said values. In some embodiments, the glass composition may contain SiO2 in an amount of 56 mol% or more, 57 mol% or more, 58 mol% or more, 59 mol% or more, 60 mol% or more, 61 mol% or more, 62 mol% or more, 63 mol% or more, 64 mol% or more, 65 mol% or more, 66 mol% or more, 67 mol% or more, 68 mol% or more, 69 mol% or more, or 70 mol% or more. In some embodiments, the glass composition may contain SiO2 in an amount of 69 mol% or less, 68 mol% or less, 67 mol% or less, 66 mol% or less, 65 mol% or less, 64 mol% or less, 63 mol% or less, 62 mol% or less, 61 mol% or less, 60 mol% or less, 59 mol% or less, 58 mol% or less, 57 mol% or less, 56 mol% or less, or 55 mol% or less.

[0060] Any of the above SiO2 ranges may be combined with any other ranges. For example, in some embodiments, the glass composition may contain SiO2 in amounts of all ranges and sub-ranges between the aforementioned values ​​having any two of the SiO2 values ​​listed above, including the endpoint, 55 mol% to 70 mol%, 56 mol% to 69 mol%, 57 mol% to 68 mol%, 58 mol% to 67 mol%, 59 mol% to 66 mol%, 60 mol% to 65 mol%, 61 mol% to 64 mol%, or 62 mol% to 63 mol%. In some embodiments, the glass composition may contain SiO2 in the range of 59 mol% to 66 mol%. In some embodiments, the glass composition may contain SiO2 in the range of 60 mol% to 65 mol%.

[0061] The glass composition disclosed in this specification includes Al2O3. The addition of Al2O3 can serve as a glass network forming agent. Additionally, when the concentration of Al2O3 is balanced with the concentrations of SiO2 and alkali oxides, the liquidus temperature of the glass melt can be lowered to improve the liquidus viscosity.

[0062] In some embodiments, the mol% of Al2O3 plus the mol% of RO in the composition (Al2O3 mol% + RO mol%) may be 18 mol% or more. In some embodiments, Al2O3 mol% + RO mol% may include 18 mol% or more and 23 mol% or less, and all ranges and sub-ranges between said values ​​(e.g., 23 mol% ≥ Al2O3 mol% + RO mol% ≥ 18 mol%). In some embodiments, Al2O3 mol% + RO mol% may be 19 mol% or more, 20 mol% or more, 21 mol% or more, or 22 mol% or more. In some embodiments, Al2O3 mol% + RO mol% may be 22 mol% or less, 21 mol% or less, 20 mol% or less, or 19 mol% or less. In the above formula, RO mol% is equal to MgO mol% + CaO mol%.

[0063] Any of the above ranges may be combined with any other ranges. For example, in some embodiments, Al2O3 mol% + RO mol% may be 18 mol% to 23 mol%, 19 mol% to 22 mol%, or 20 mol% to 21 mol%, and any two of the values ​​listed above as endpoints, including any two of the above values. In some embodiments, Al2O3 mol% + RO mol% may be 20 mol% or more.

[0064] As stated above (Al2O3 The mol% + RO mol%) value is advantageous for the glass composition disclosed herein. With the (Al2O3 mol% + RO mol%) value as described above, the glass composition can achieve high peak compressive stress over a wide range of compression depths as discussed herein. (Al2O3 If mol% + RO mol%) is less than 18 mol%, preferably, high ion exchange stress may not be formed. If (Al2O3 mol% + RO mol%) exceeds 23 mol%, the ion exchange process may become too slow and / or the Young's modulus may be undesirably high. Additionally, the manufacturability of the glass composition may suffer from values ​​exceeding 23 mol%.

[0065] In some embodiments, the glass composition may contain Al2O3 at a concentration of 13 mol% or more to 20 mol% or less, and may be any range and sub-range between the aforementioned values. In some embodiments, the glass composition may contain Al2O3 in an amount of 13 mol% or more, 13.5 mol% or more, 14 mol% or more, 14.5 mol% or more, 15 mol% or more, 15.5 mol% or more, 16 mol% or more, 16.5 mol% or more, 17 mol% or more, 17.5 mol% or more, 18 mol% or more, 18.5 mol% or more, 19 mol% or more, 19.5 mol% or more, or 20 mol% or more. In some embodiments, the glass composition may contain Al2O3 in an amount of 20 mol% or less, 19.5 mol% or less, 19 mol% or less, 18.5 mol% or less, 18 mol% or less, 17.5 mol% or less, 17 mol% or less, 16.5 mol% or less, 16 mol% or less, 15.5 mol% or less, 15 mol% or less, 14.5 mol% or less, 14 mol% or less, 13.5 mol% or less, or 13 mol%.

[0066] Any of the above Al2O3 ranges may be combined with any other ranges. For example, in some embodiments, the glass composition may contain Al2O3 in amounts of all ranges and sub-ranges between said values, including 13 mol% to 20 mol%, 13.5 mol% to 19.5 mol%, 14 mol% to 19 mol%, 14.5 mol% to 18.5 mol%, 15 mol% to 18.5 mol%, 15.5 mol% to 17.5 mol%, or 16 mol% to 17 mol%, and an endpoint, with any two of the listed Al2O3 values ​​as the endpoint. In some embodiments, the glass composition may contain Al2O3 in an amount of 13.5 mol% to 20 mol%. In some embodiments, the glass composition may contain Al2O3 in an amount of 16 mol% or more. In some embodiments, the glass composition may contain Al2O3 in an amount of 16 mol% to 18 mol%.

[0067] The glass compositions described herein include Na2O. Na2O can improve manufacturability by assisting the ion exchangeability of the glass compositions and improving the moldability of the glass compositions. However, if too much Na2O is added to the glass compositions, the CTE may be too low and the melting point too high. In some embodiments, the glass compositions may include Na2O at concentrations ranging from 15 mol% to 18 mol% and including any two of the values ​​listed above as endpoints, and at all ranges and sub-ranges between said values. In some embodiments, the glass compositions may include Na2O in amounts of 15 mol% or more, 15.5 mol% or more, 16 mol% or more, 16.5 mol% or more, 17 mol% or more, 17.5 mol% or more, or 18 mol%. In some embodiments, the glass composition may contain Na2O in an amount of 18 mol% or less, 17.5 mol% or less, 17 mol% or less, 16.5 mol% or less, 16 mol% or less, 15.5 mol% or less, or 15 mol% or less.

[0068] Any of the above Na2O ranges may be combined with any other ranges. For example, in some embodiments, the glass composition may contain Na2O in amounts of all ranges and sub-ranges between the values, including 15.5 mol% to 17.5 mol%, 16 mol% to 17 mol%, or 16.5 mol% to 17 mol%, with any two of the Na2O values ​​listed above as endpoints.

[0069] In some embodiments, the mol% of Na2O + mol% of RO - mol% of Al2O3 (Na2O mol% + RO mol% - Al2O3 mol%) for the glass composition is 0 mol% or more. In some embodiments, the mol% of Na2O + mol% of RO - mol% of Al2O3 may be 0 mol% or more and 7 mol% or less (e.g., 7 mol% ≥ (Na2O mol% + RO mol% - Al2O3 mol%) ≥ 0 mol%), and may include all ranges and sub-ranges between the above values. In some embodiments, the mol% of Na2O + mol% of RO - mol% of Al2O3 may be 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more, 5 mol% or more, or 6 mol% or more. In some implementation examples, Na2O mol% + RO mol% - Al2O3 mol% may be 7 mol% or less, 6 mol% or less, 5 mol% or less, 4 mol% or less, 3 mol% or less, 2 mol% or less, or 1 mol% or less. In the above formula, RO mol% is equal to MgO mol% + CaO mol%.

[0070] Any of the above ranges may be combined with any other ranges. For example, in some embodiments, Na2O mol% + RO mol% - Al2O3 may be any range and sub-range between the aforementioned values ​​having any two of the values ​​listed above as endpoints, including 1 mol% to 6 mol%, 2 mol% to 5 mol%, or 3 mol% to 4 mol%.

[0071] The (Na2O mol% + RO mol% - Al2O3 mol%) value described above is advantageous to the glass composition disclosed herein. With the (Na2O mol% + RO mol% - Al2O3 mol%) value described above, the glass composition exhibits the following advantageous properties. First, adjusting the (Na2O mol% + RO mol% - Al2O3 mol%) value as described above improves the meltability of the glass composition. The (Na2O mol% + RO mol% - Al2O3 mol%) value produces advantageous thermal properties, such as the liquidus temperature and liquidus viscosity discussed herein, thereby increasing the ease of manufacturing glass articles produced from the composition. If the (Na2O mol% + RO mol% - Al2O3 mol%) value is less than 0 mol%, the meltability of the glass composition is reduced. Second, as explained above, adjusting the value (Na2O mol% + RO mol% - Al2O3 mol%) allows for the creation of an ion exchange window capable of generating a desired compositional gradient, while avoiding significant stress relief in the glass article corresponding to the compressive stress imparted by the ion exchange process. If the value (Na2O mol% + RO mol% - Al2O3 mol%) exceeds 7 mol%, a significant amount of stress relationship may occur within the glass article during the ion exchange process. This stress relief reduces the compressive stress, particularly the peak compressive stress imparted during the ion exchange process.

[0072] The glass compositions described herein contain MgO. MgO can improve the formability and manufacturability of the glass by lowering the viscosity of the glass. Including MgO in the glass composition can improve the deformation point, Young's modulus, and ion exchange capacity of the glass composition. However, if too much MgO is added to the glass composition, the density and CTE of the glass composition may increase to undesirable levels.

[0073] In some embodiments, the glass composition may contain MgO at a concentration of 1 mol% or more to 5 mol% or less, and in all ranges and sub-ranges between the aforementioned values. In some embodiments, the glass composition may contain MgO in an amount of 1.5 mol% or more, 2 mol% or more, 2.5 mol% or more, 3 mol% or more, 3.5 mol% or more, 4 mol% or more, 4.5 mol% or more, or 5 mol%. In some embodiments, the glass composition may contain MgO in an amount of 4.5 mol% or less, 4 mol% or less, 3.5 mol% or less, 3 mol% or less, 2.5 mol% or less, 2 mol% or less, 1.5 mol% or less, or 1 mol%.

[0074] Any of the above MgO ranges may be combined with any other ranges. For example, in some embodiments, the glass composition may contain MgO in amounts of all ranges and sub-ranges between the aforementioned values, including 1 mol% to 5 mol%, 1.5 mol% to 4.5 mol%, 2 mol% to 4 mol%, 2.5 mol% to 3.5 mol%, or 2.5 mol% to 3 mol%, and any two of the MgO values ​​listed above as endpoints. In some embodiments, the glass composition may contain MgO in the range of 2 mol% to 4 mol%.

[0075] The glass compositions described herein contain CaO. CaO can lower the viscosity of the glass to improve formability, deformation point, and Young's modulus, and can also improve the ion exchange capacity of the glass. However, if too much CaO is added to the glass composition, the density and CTE of the glass composition may increase to undesirable levels.

[0076] In some embodiments, the glass composition may contain CaO at a concentration of 0.1 mol% or more to 2.5 mol% or less, and in all ranges and sub-ranges between the above values. In some embodiments, the glass composition may contain CaO in an amount of 0.5 mol% or more, 1 mol% or more, 1.5 mol% or more, 2 mol% or more, or 2.5 mol%. In some embodiments, the glass composition may contain CaO in an amount of 2.5 mol% or less, 2 mol% or less, 1.5 mol% or less, 1 mol% or less, 0.5 mol% or less, or 0.1 mol%.

[0077] Any of the above ranges may be combined with any other ranges. For example, in some embodiments, the glass composition may contain CaO in amounts of 0.1 mol% to 2.5 mol%, 0.5 mol% to 2 mol%, or 1 mol% to 1.5 mol%, and all ranges and sub-ranges between said values ​​having any two of the CaO values ​​listed above as endpoints, including endpoints. In some embodiments, the glass composition may contain CaO in the range of 0.5 mol% to 2 mol%.

[0078] In some embodiments, the mol% of MgO to the mol% of MgO plus the mol% of CaO for the glass composition (MgO mol% / (MgO mol% + CaO mol%)) may be 0.5 or greater. In some embodiments, MgO mol% / (MgO mol% + CaO mol%) may be 0.5 or greater and 0.9 or less (e.g., 0.9 ≥ (MgO mol% / (MgO mol% + CaO mol) %)) ≥ 0.5), and may include all ranges and sub-ranges between the aforementioned values. In some embodiments, MgO mol% / (MgO mol% + CaO mol%) may be 0.55 or greater, 0.6 or greater, 0.65 or greater, 0.7 or greater, 0.7 or greater, 0.75 or greater, 0.8 or greater, 0.85 or greater, or 0.9 or greater. In some implementation examples, MgO mol% / (MgO mol% + CaO mol%) may be 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.55 or less, or 0.5 or less.

[0079] Any of the above ranges may be combined with any other ranges. For example, in some embodiments, MgO mol% / (MgO mol% + CaO mol%) may be any range and sub-range between the aforementioned values ​​having any two of the values ​​listed above as endpoints, including 0.5 to 0.9, 0.55 to 0.85, 0.6 to 0.8, 0.65 to 0.75, or 0.65 to 0.7.

[0080] The glass compositions described herein may be absent or substantially absent of one or more of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O. In some embodiments, the glass compositions may be all or substantially absent of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O. Some of these oxides may be expensive and / or have limited supply. Alkaline earth metal oxides can undesirably increase Young's modulus and slow down the ion exchange process. B2O3, P2O5, and K2O can reduce the amount of compressive stress imparted during the ion exchange process. The glass articles described herein can achieve advantageous properties without the need for these oxides. Therefore, these oxides may be excluded from the composition. As used herein, the term "substantially absent" means that the component is not added as a component of the batch material, even though the component may be present in very small amounts as a contaminant in the final glass. Certain impurities or components that were not intentionally added may be present in the final glass composition as a result of the raw materials and / or equipment used to manufacture the glass compositions described herein. These materials are present in the glass composition in small amounts, referred to as "tramp materials." A composition "substantially free" of a component means that the component was not intentionally added to the composition, but the composition may still contain trace amounts of the component. A composition "substantially free" of oxide means that oxides are present in an amount of 0.1 mol% or less, for example, from 0 mol% to 0.1 mol%. As used herein, a glass composition "free" of a component is defined to mean that the component (e.g., oxide) is not present in the composition even in trace amounts.

[0081] In some embodiments, the glass composition may optionally include one or more clarifying agents. In some embodiments, the clarifying agent may include, for example, SnO2. In these embodiments, SnO2 may be present in the glass composition in an amount of 2 mol% or less, for example, from 0 mol% to 2 mol%, and in all ranges and sub-ranges between the aforementioned values. In some embodiments, SnO2 may be present in the glass composition in an amount of 0.1 mol% to 2 mol%, 0.1 mol% to 1.5 mol%, 0.1 mol% to 1 mol%, or 0.1 mol% to 0.5 mol%.

[0082] The physical properties of the glass composition disclosed in this specification and the glass articles made from the glass composition are discussed below. These physical properties can be achieved by adjusting the amount of the components of the glass composition, as discussed in more detail with reference to the examples.

[0083] In some embodiments, the Young's modulus (E) of the glass composition may be 70 gigapascals (GPa) or more and 80 GPa or less, and may be any range and sub-range between the aforementioned values. In some embodiments, the glass composition may have a Young's modulus of any range and sub-range between the values, such as 71 GPa or more and 79 GPa or less, 72 GPa or more and 78 GPa or less, 73 GPa or more and 77 GPa or less, 74 GPa or more and 76 GPa or less, or 75 GPa or more and 76 GPa or less, and any two of the Young's modulus values ​​listed above as endpoints, including endpoints. For example, in some embodiments, the glass composition may have a Young's modulus in the range of 70 GPa to 80 GPa, 71 GPa to 79 GPa, 72 GPa to 78 GPa, 73 GPa to 77 GPa, 74 GPa to 76 GPa, or 75 GPa to 76 GPa. In some embodiments, the glass composition may have a Young's modulus in the range of 70 GPa to 75 GPa. Unless otherwise specified, the Young's modulus and Poisson's ratio values ​​disclosed herein refer to values ​​measured by the general type resonant ultrasound spectroscopy specified in ASTM E2001-13, "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts." Additionally, unless otherwise specified, the Young's modulus and Poisson's ratio of the glass composition or article are measured before the composition or article undergoes an ion exchange process or other strengthening process. In particular, the Young's modulus and Poisson's ratio of a glass composition or article are measured before the composition or article is exposed to an ion exchange solution, for example, before being immersed in the ion exchange solution. The Poisson's ratio value (v) is calculated based on the Young's modulus value (E) and the shear modulus value (G) obtained from the ASTM E2001-13 test using the following formula: E = 2G(1+v).

[0084] In some embodiments, the liquidus viscosity of the glass composition may be 50 kP or more and 500 kP or less, and may be any range and sub-range between the aforementioned values. In some embodiments, the glass composition may have a liquidus viscosity of any range and sub-range between the values, such as 100 kP or more and 450 kP or less, 150 kP or more and 400 kP or less, 200 kP or more and 350 kP or less, or 250 kP or more and 300 kP or less, and any two of the liquidus viscosity values ​​listed above as endpoints, including endpoints. For example, in some embodiments, the glass composition may have a liquidus viscosity in the range of 50 kP to 500 kP, 100 kP to 450 kP, 150 kP to 400 kP, 200 kP to 350 kP, or 250 kP to 300 kP.

[0085] As used herein, the term “liquidus viscosity” refers to the viscosity of molten glass at the liquidus temperature, where the liquidus temperature means the temperature at which crystals first appear when molten glass is cooled from its melting temperature, or the temperature at which the last crystals melt as the temperature increases from room temperature. Unless otherwise specified, the liquidus viscosity values ​​disclosed in this application are determined by the following methods. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015), “Standard Practice for Measurement of Glass of Liquidus Temperature of the Gradient Furnace Method.” Next, the viscosity of the glass at the liquidus temperature is measured according to ASTM C965-96 (2012), titled “Standard Practice for Measuring Viscosity of Glass Above the Softening Point.” Unless otherwise specified, the liquidus viscosity and temperature of the glass composition or article are measured before the composition or article undergoes an ion exchange process or other strengthening process. In particular, the liquidus viscosity and temperature of the glass composition or article are measured before the composition or article is exposed to an ion exchange solution, for example, before being immersed in an ion exchange solution.

[0086] From the above composition, a glass article according to an embodiment may be formed by any suitable method, e.g., slot forming, float forming, rolling process, fusion forming process, etc. The glass composition and the article made therefrom may be characterized in a manner that allows them to be formed. For example, the glass composition may be characterized as float formability (i.e., formed by a float process), downward drawingability, particularly fusion formingability or slot drawingability (e.g., fusion drawing process or slot drawing process).

[0087] Some embodiments of the glass articles described herein may be formed by a downward drawing process. The downward drawing process produces glass articles of uniform thickness with a relatively clean surface. Since the average bending strength of the glass articles is controlled by the amount and size of surface defects, a clean surface with minimal contact has higher initial strength. Additionally, downward drawn glass articles have a very flat and smooth surface that can be used for final applications without expensive grinding and polishing.

[0088] Some embodiments of glass articles can be described as fusion-formable (i.e., formable using a fusion drawing process). The fusion process utilizes a drawing tank with a channel for receiving molten glass raw material. The channel has weirs open at the top along the length of the channel on both sides. When the channel is filled with molten material, the molten glass overflows the weirs. Due to gravity, the molten glass flows under the outer surface of the drawing tank as two flowing glass films. These outer surfaces of the drawing tank extend downward and inward so that they join at the edge below the drawing tank. The two flowing glass films join at this edge to form and fuse into a single flowing glass article. The fusion drawing method offers the advantage that none of the outer surfaces of the resulting glass article come into contact with any part of the device because the two glass films flowing over the channel are fused together. Therefore, the surface properties of the fusion-drawn glass article are not affected by such contact.

[0089] Some embodiments of the glass articles described herein may be formed by a slot drawing process. The slot drawing process is different from the fusion drawing method. In the slot drawing process, molten raw glass is supplied to a drawing tank. At the bottom of the drawing tank, there is an open slot with a nozzle that extends the length of the slot. The molten glass flows through the slot and / or nozzle and is drawn downward as a continuous glass article and into an annealing zone.

[0090] The drawing process for forming glass articles, such as glass sheets, is desirable because it can form thin glass articles with few defects. Previously, it was thought that glass compositions had to have a relatively high liquidus viscosity (e.g., greater than 1000 kP, greater than 1100 kP, or greater than 1200 kP) to be formed by the drawing process, such as fusion drawing or slot drawing. However, with advancements in the drawing process, glass with a low liquidus viscosity can be used in the drawing process.

[0091] In one or more embodiments, the glass article described herein may exhibit an amorphous microstructure and may be substantially free of crystals or crystallites. In other words, the glass article excludes glass-ceramic materials in some embodiments. In some embodiments, the glass article described herein may include glass-ceramic materials.

[0092] As mentioned above, the glass composition and the article made from the glass composition can be strengthened by an ion-exchange process. Referring to FIG. 1, the glass article (100) may have one or more regions under compressive stress. For example, the glass article (100) may have a first compressive stress region (120) and / or a second compressive stress region (122) extending from the outer surface of the glass article (100) (e.g., surface (110, 112)) to a compression depth (DOC, d1, d2) and a second region under CT or tensile stress extending from the DOC to the center or inner region of the glass article (100) (e.g., center region (130)). The ion-exchange compressive stress regions (120, 122) have different concentrations of metal oxides at two or more points along the thickness (t) of the glass article (100).

[0093] According to convention commonly used in the art, compression or compressive stress (CS) is expressed as negative (<0) stress, and tension or tensile stress is expressed as positive (>0) stress. However, throughout this description, CS is expressed as a positive or absolute value. That is, as cited herein, CS = |CS|. CS may have a maximum value at the surface of the glass and may vary depending on the distance (d) from the surface according to the function. Referring again to FIG. 1, the first compressive stress region (120) extends from the first surface (110) to a depth d1, and the second compressive stress region (122) extends from the second surface (112) to a depth d2. Together, these compressive stress regions (120, 122) define the compression region or CS region of the glass article (100).

[0094] In some embodiments, the peak compressive stress of one or more compressive stress regions of the glass article may be 850 MPa or more and 1400 megapascals (MPa) or less, e.g. 900 MPa or more and 1350 MPa or less, 950 MPa or more and 1300 MPa or less, 1000 MPa or more and 1250 MPa or less, 1050 MPa or more and 1200 MPa or less, or 1100 MPa or more and 1150 MPa or less, and all ranges and sub-ranges between said values ​​having any two of the values ​​listed above as endpoints, including endpoints. For example, in some embodiments, the peak compressive stress may be within a range of 850 MPa to 1400 MPa, 900 MPa to 1350 MPa, 950 MPa to 1300 MPa, 1000 MPa to 1250 MPa, 1050 MPa to 1200 MPa, or 1100 MPa to 1150 MPa, or any two of these values ​​as endpoints. In some embodiments, the peak compressive stress of one or more compressive stress regions of the glass article may be in the range of 1100 MPa to 1350 MPa.

[0095] In some embodiments, a glass article produced from a glass composition may have a ratio of the peak compressive stress value to the Young's modulus value of 14 or more (peak compressive stress value / Young's modulus value, CS / E). In some embodiments, the glass article may have a CS / E ratio in the range of 14 or more to 18 or less, and all ranges and sub-ranges between the aforementioned values. In some embodiments, the glass article may have a CS / E ratio of 15 or more, 16 or more, 17 or more, or 18. In some embodiments, the glass article may have a CS / E ratio of 18 or less, 17 or less, 16 or less, 15 or less, or 14. Any of the above CS / E ranges may be combined with any other range. For example, in some embodiments, the CS / E ratio may be 14 to 18, 15 to 17, or 15 to 16, and may be any range and sub-range between said values, including an endpoint, having any two of the values ​​listed above as endpoints. In some embodiments, the glass article may have a CS / E ratio of 15 or more.

[0096] These CS / E ratios and CS / E ratio ranges may be achieved at peak compressive stress and / or compression depths described herein. For example, in some embodiments, a glass article may have a CS / E ratio or CS / E ratio range as described above, with a peak compressive stress in the range of 850 MPa to 1400 MPa. As another example, a glass article may have a CS / E ratio or CS / E ratio range as described above, with a compression depth in the range of 5 microns to 40 microns. As another example, a glass article may have a CS / E ratio or CS / E ratio range as described above, with a compression depth in the range of 5 microns to 20 microns. As another example, a glass article may have a CS / E ratio or CS / E ratio range as described above, with a compression depth in the range of 5% to 20% of the thickness of the glass article. As another example, the glass article may have a CS / E ratio or a CS / E ratio range as described above, with a peak compressive stress in the range of 1100 MPa to 1350 MPa and a compression depth in the range of 5 microns to 20 microns. As another example, the glass article may have a CS / E ratio or a CS / E ratio range as described above, with a peak compressive stress in the range of 850 MPa to 1400 MPa and a compression depth in the range of 5 microns to 40 microns. As another example, the glass article may have a CS / E ratio or a CS / E ratio range as described above, with a peak compressive stress in the range of 850 MPa to 1400 MPa and a compression depth in the range of 5 microns to 20 microns.

[0097] The high peak compressive stress achievable by ion exchange provides the ability to bend the glass to a tighter (i.e., smaller) bending radius for a given glass thickness. This high peak compressive stress causes the glass to maintain net compression, which includes surface defects when the glass is bent around a narrow radius. Near-surface defects cannot extend to fracture if they are contained within this net compression state or positioned within the effective surface compression layer.

[0098] FIG. 2 illustrates a two-point bending of a glass article (100) between two plates (200) using a bending force (202). The bending force (202) is applied using a two-point bending test device in which two plates (200) are pressed against the glass article (100) during the bending test with a constant bending force (202). If necessary, a fixture associated with the test device ensures that the glass article (100) bends symmetrically with respect to the folding line (210) when the bending force (202) is applied to the glass article (100) through the plates (200). The plates (200) may be moved together simultaneously until a specific plate distance D is reached. As used herein, the term “breakage” under a bending force refers to breakage, destruction, delamination, crack propagation, permanent deformation, or any other mechanism that renders the article unsuitable for its intended purpose.

[0099] As illustrated in FIG. 2, the surface (110) of the glass article (100) is subjected to tensile stress due to bending, and while the effective DOC from the surface when the article is not bent is reduced from the DOC from the surface (110), the surface (112) is subjected to additional compressive stress due to bending. The effective DOC from the surface (110) increases as the plate distance increases and decreases as the plate distance decreases (when the surface (112) of the article (100) is bent toward itself as illustrated in FIG. 2). That is, the effective DOC is the value obtained by subtracting the effective depth of tensile stress due to bending from the DOC in the unbent state.

[0100] In some embodiments, the glass article (100) avoids breakage during a static two-point bending test when held between two plates (200) for 240 hours at 60°C and 93% relative humidity with a plate distance (D) of 10 millimeters (mm) or less. For example, in some embodiments, the glass article (100) avoids breakage during a static two-point bending test when held between two plates for 240 hours at 60°C and 93% relative humidity with a plate distance (D) of 10 mm to 1 mm. The plate distance (D) may be, for example, 10 mm, 9 mm, 8 mm, 7 mm, 6 mm, 5 mm, 4 mm, 3 mm, 2 mm, or 1 mm.

[0101] The compressive stress in the two regions (120, 122) is balanced by the tension stored in the central region (130) of the glass article (100). Unless otherwise specified, the CT value is reported as the maximum CT value. The DOC can be measured by a surface stress meter or a scattering polarizer (SCALP) depending on the ion exchange treatment and the thickness of the article being measured. If stress is generated in the substrate by exchanging potassium ions into the substrate, the compressive depth is measured using a surface stress meter, e.g., FSM-6000 (Orihara Industrial Co., Ltd., Japan). If stress is generated by exchanging sodium ions into the substrate and the product being measured is thicker than about 400 microns, SCALP is used to measure the compressive depth and maximum central tension (CT). If stress is generated in the substrate by exchanging potassium and sodium ions into the glass and the product being measured is thicker than about 400 microns, the compressive depth and CT are measured by SCALP. Without being bound by theory, the exchange depth of sodium may represent the compression depth, while the exchange depth of potassium ions may represent a change in the magnitude of compressive stress (but not necessarily a change in stress from compression to tension). As used herein, “layer depth” refers to the depth to which ions (e.g., sodium, potassium) are exchanged into the substrate. For the purposes of this specification, where the maximum center tension cannot be directly measured by SCALP (such as when the article being measured is thinner than about 400 microns), the maximum center tension may be approximated as the product of the peak compressive stress and the compression depth divided by the difference between the substrate thickness and the compression depth, where the compressive stress and compression depth are measured by FSM.

[0102] When the substrate thickness is greater than about 400 microns, the refracted near-field (RNF) method may be used to derive a graphical representation of the stress profile. When deriving a graphical representation of the stress profile using the RNF method, the maximum CT value provided by SCALP is utilized in the RNF method. In particular, the stress profile measured by RNF is balanced by forces and corrected by the maximum CT value provided by the SCALP measurement. The RNF method is described in U.S. Patent No. 8,854,623, titled “Systems and methods for measuring a profile characteristic of a glass sample,” which is incorporated herein by reference in its entirety. In particular, the RNF method comprises the steps of placing a glass article adjacent to a reference block, generating a polarization-switched light beam that switches between orthogonal polarizations at a rate of 1 Hz to 50 Hz, measuring the power of the polarization-switched light beam, and generating a polarization-switched reference signal, wherein the power measured in each orthogonal polarization is within 50% of each other. The above method further comprises the step of transmitting a polarization-switched light beam into a glass sample and a reference block at different depths into the glass sample, and then relaying the transmitted polarization-switched light beam to a signal photodetector using a relay optical system, wherein the signal photodetector generates a polarization-switched detector signal. The method also comprises the step of splitting the detector signal into a reference signal to form a normalized detector signal, and the step of determining the profile characteristics of the glass sample from the normalized detector signal.

[0103] When SCALP measurements are performed, they are carried out using a SCALP polarimeter (e.g., SCALP-04 or SCALP-05) available from GlassStress Ltd. in Tallinn, Estonia. When measuring samples to characterize one or more stress-related properties, the precise sample rate SS and exposure time tE required to reduce the measurement noise of the polarimeter to an acceptable level depend on several factors. These factors include characteristics of the image sensor (e.g., gain, image capture rate (frames / second), pixel size, internal pixel averaging technique, etc.) and characteristics such as stress-free (NSR) scattering properties, the intensity of the input light, and the number of polarization states used. Other factors include the measurement wavelength of the light emanating from the laser source and the intensity of the scattered light. Exemplary measurement wavelengths may include 640 nanometers (nm), 518 nm, and 405 nm. Examples of exposure times are between 0.05 milliseconds and 100 milliseconds. The example frame rate can range from 10 to 200 frames per second. An exemplary calculation of optical delay is performed over a measurement time t of 0.1 to 10 seconds. M 2 to 200 frames can be used over time.

[0104] In some embodiments, the glass article may have a maximum CT of all ranges and sub-ranges between said values, including an endpoint, having any two of the values ​​listed above as endpoints, such as 20 MPa or more and 400 MPa or less, e.g., 50 MPa or more and 350 MPa or less, 75 MPa or more and 300 MPa or less, 100 MPa or more and 250 MPa or less, or 150 MPa or more and 200 MPa or less. For example, in some embodiments, the maximum CT may be a range of 20 MPa to 400 MPa, 50 MPa to 350 MPa, 75 MPa to 300 MPa, 100 MPa to 250 MPa, or 150 MPa to 200 MPa, or a range having two of these values ​​as endpoints.

[0105] In some embodiments, the DOC of region (120) and / or region (122) may be a range of 5 microns to 50 microns, including sub-ranges. For example, the DOC may be a range of 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, or 50 microns, or a range having any two of these values ​​as endpoints, including endpoints. In some embodiments, the DOC of region (120) and / or region (122) may be a range of 10 microns to 45 microns, 15 microns to 40 microns, 20 microns to 35 microns, or 25 microns to 30 microns. In some embodiments, the DOC may be in the range of 5 microns to 40 microns. In some embodiments, the DOC may be in the range of 5 microns to 20 microns.

[0106] In some embodiments, the DOC may be reported as part of the thickness (t) of the glass article (100). In some embodiments, the glass article may have a depth of compression (DOC) ranging from 5% (0.05t) or more of the glass article thickness to 20% (0.20t) or less of the glass article thickness, and all ranges and sub-ranges between the aforementioned values. In some embodiments, the DOC may be 5% to 20% of the thickness of the glass article, 5% to 10% of the thickness of the glass article, or 5% to 15% of the thickness of the glass article.

[0107] The thickness (t) of the glass article (100) is measured between the surface (110) and the surface (112). In some embodiments, the thickness of the glass article (100) may be 4 millimeters (mm) or less. In some embodiments, the thickness of the glass article (100) may be in the range of 15 microns to 4 mm, including a sub-range. For example, the thickness of the glass article (100) may be in the range of 15 microns, 20 microns, 30 microns, 50 microns, 75 microns, 100 microns, 150 microns, 200 microns, 250 microns, 500 microns, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, or having two of these values ​​including the end point. In some embodiments, the thickness of the glass article (100) may be in the range of 20 microns to 3.5 mm, 30 microns to 3 mm, 50 microns to 2.5 mm, 75 microns to 2 mm, 100 microns to 1.5 mm, 150 microns to 1 mm, 200 microns to 500 microns, or 200 microns to 250 microns. In some embodiments, the thickness of the glass article (100) may be in the range of 15 microns to 200 microns. In some embodiments, the thickness of the glass article (100) may be in the range of 15 microns to 100 microns.

[0108] A compressive stress layer can be formed on a glass article by exposing the glass article to an ion exchange solution. In some embodiments, the ion exchange solution may comprise a molten potassium salt. In some embodiments, the ion exchange solution may comprise 50 wt% or more of a potassium salt, 60 wt% or more of a potassium salt, 70 wt% or more of a potassium salt, 80 wt% or more of a potassium salt, 90 wt% or more of a potassium salt, or 100 wt% of a potassium salt, and all ranges between and below the above values ​​of a potassium salt. In some embodiments, the ion exchange solution may comprise 50 wt% to 100 wt% of a potassium salt, 60 wt% to 100 wt% of a potassium salt, 70 wt% to 100 wt% of a potassium salt, 80 wt% to 100 wt% of a potassium salt, or 90 wt% to 100 wt% of a potassium salt. In some embodiments, the potassium salt may be KNO3. In some embodiments, all or part of the weight percentage remaining in the ion exchange solution may be molten nitrate, for example, NaNO3.

[0109] A glass article may be exposed to an ion exchange solution by immersing a glass article made of a glass composition in a bath of ion exchange solution, spraying the ion exchange solution onto a glass article made of a glass composition, or otherwise physically applying the ion exchange solution to the glass article. When exposed to the glass article, the ion exchange solution may be at a temperature of 350°C or higher and 480°C or lower, and all ranges and sub-ranges between the above values, depending on the embodiment. In some embodiments, the temperature may be 360°C or higher and 470°C or lower, 370°C or higher and 460°C or lower, 380°C or higher and 450°C or lower, 390°C or higher and 440°C or lower, 400°C or higher and 430°C or lower, or 410°C or higher and 420°C or lower, and all ranges and sub-ranges between the above values, including two of the temperature values ​​listed above as endpoints. In some embodiments, the temperature of the ion exchange solution may be in the range of 350°C to 480°C, 360°C to 470°C, 370°C to 460°C, 380°C to 450°C, 390°C to 440°C, 400°C to 430°C, or 410°C to 420°C.

[0110] In some embodiments, the glass article may be exposed to an ion exchange solution for a period of 1 hour or more and 24 hours or less, and for any range and sub-range between the aforementioned values. In some embodiments, the duration may be 2 hours or more and 20 hours or less, 4 hours or more and 16 hours or less, 6 hours or more and 12 hours or less, or 8 hours or more and 12 hours or less, and any two of the time values ​​listed above as endpoints, including endpoints, and for any range and sub-range between said values. In some embodiments, the glass article may be exposed to an ion exchange solution for 1 hour or 24 hours, 2 hours or more and 20 hours, 4 hours or more and 16 hours, or 8 hours or more and 12 hours. In some embodiments, the duration may be in the range of 1 hour or 10 hours, or 2 hours or more and 8 hours.

[0111] It should be understood that after the ion exchange process is performed, the composition on the surface of the glass article may differ from the composition of the formed glass article (e.g., the glass article before the ion exchange process). This occurs because one type of alkali metal ion in the formed glass, such as Na+, is replaced by a larger alkali metal ion, such as K+. However, in some embodiments, the glass composition at or near the depth center of the glass article will still have the composition of the glass article as formed. Unless otherwise specified, the glass composition disclosed in this application is the composition of the glass article near the depth center of the article where the composition is not (or is least affected) by the ion exchange process, i.e., the composition of the glass article as formed.

[0112] The glass articles described herein may be incorporated into other articles, for example, articles having a display (or display articles) (e.g., consumer electronic products including mobile phones, watches, tablets, computers, navigation systems, etc.), construction articles, transport articles (e.g., automobiles, trains, aircraft, ships, etc.), home appliances, or any article that can obtain some transparency, scratch resistance, wear resistance, or a combination thereof. An exemplary article comprising any glass article disclosed herein is illustrated in FIGS. 3a and 3b. Specifically, FIGS. 3a and 3b illustrate a consumer electronic product (300) comprising a housing (302) having a front (304), a rear (306), and a side (308). Electrical components located at least partially or wholly inside the housing on or adjacent to the front (306) of the housing (302) may include at least a controller (320), a memory (322), and a display (310). The display (310) may be, for example, a light-emitting diode (LED) display or an organic light-emitting diode (OLED) display.

[0113] A cover substrate (312) may be placed on or over the front surface (304) of the housing (302) so as to be placed over the display (310). The cover substrate (312) may serve to protect the display (310) and other components of the consumer electronics (300) (e.g., a controller (320) and a memory (322)) from damage. In some embodiments, the cover substrate (312) may be bonded to the display (310) with an adhesive. In some embodiments, the cover substrate (312) may define all or part of the front surface (304) of the housing (302). In some embodiments, the cover substrate (312) may define all or part of the front surface (304) of the housing (302) and the side surface (308) of the housing (302). In some embodiments, the consumer electronics (300) may include a cover substrate that defines all or part of the rear surface (306) of the housing (302).

[0114] Example of implementation

[0115] Implementation examples will be made clearer by the following examples. It should be understood that these examples are not limited to the implementation examples described above.

[0116] Glass compositions having the components listed in Table 1 below were prepared by a conventional glass molding method. Compositions 1 to 4 in Table 1 are glass compositions according to embodiments of the present application. Composition A in Table 1 is a comparative composition prepared from a similar oxide. All components in Table 1 are in mol%. The SC and CT values ​​reported in Table 1 were measured for each composition at the sample thickness reported in the table.

[0117] Table 2 lists the material properties of the compositions in Table 1. The Young's modulus (E) values ​​reported in Table 2 were measured according to the methods disclosed herein. Similarly, the shear modulus values ​​were measured by the general type of resonant ultrasound spectroscopy technique specified in ASTM E2001-13, titled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts."

[0118] Additional material properties listed in Table 2 include: density, where density values ​​were determined using the buoyancy method of ASTM C693-93 (2013); low-temperature (range 0°C to 300°C) CTE measured in parts per million (ppm / °C); strain point, annealing point, and softening point, strain point was measured using the beam bending viscosity method of ASTM C598-93 (2013), annealing point was measured using the fiber elongation method of ASTM C336-71 (2015), and softening point was measured using the fiber elongation method of ASTM C338-93 (2013); 1011 Poise, 35 kP, 200 kP, and liquidus temperature; liquidus viscosity, liquidus viscosity was determined as liquid viscosity is discussed herein; and stress optical modulus (SOC) associated with the birefringence of the glass. Unless otherwise specified, SOC was measured according to Procedure C (Glass Disk Method) described in ASTM Standard C770-16, titled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein by reference in their entirety. Unless otherwise specified, the properties listed in Table 2 were measured before the composition or article underwent an ion exchange process or other strengthening process. CTE values ​​were measured using fiber elongation techniques in Table 2. The dilatometer was set according to ASTM E228 ("Standard Test Method for Linear Thermal Expansion of Solid Materials With a Push-Rod Dilatometer"). For the fiber elongation test, a fiber sample of the specific composition mounted on the dilatometer was placed in a 0°C ice bath and then placed in a 300°C isothermal furnace to determine the average linear coefficient of thermal expansion for the corresponding temperature range. The fiber samples were prepared by flame processing.

[0119] Table 3 contains the ion exchange conditions and properties for Compositions 1-4 and Composition A of Table 1. For the ion exchange process reported in Table 3, samples of each composition were immersed in a molten salt bath composed of 100 wt% KNO3. Each sample had a length of 1 inch, a width of 1 inch, and a thickness of 0.8 mm. The maximum CT values ​​reported in Table 3 were approximated as the product of the peak compressive stress and compression depth divided by the difference between the substrate thickness and compression depth, where the compressive stress and compression depth were measured by FSM.

[0120]

[0121]

[0122]

[0123]

[0124]

[0125] As shown in Table 3, compositions 1 to 4 were all able to achieve a CS / E ratio higher than that of composition A for each ion exchange time. During an ion exchange time of 2 hours, composition A achieved a DOC of 23.4 microns and a CS / E ratio of 13.69, while compositions 1-4 achieved a similar DOC and a much higher CS / E ratio. Each of compositions 1-4 achieved a DOC of 23 microns or more and a CS / E ratio of 15.53 or more (an increase of about 13.4% or more compared to composition A). During an ion exchange time of 4 hours, composition A achieved a DOC of 32.6 microns and a CS / E ratio of 13.38, while compositions 1-4 achieved a similar DOC and a much higher CS / E ratio. Each of Compositions 1-4 achieved a DOC of 32.6 microns or more and a CS / E ratio of 15.16 or more (an increase of about 13.3% or more compared to Composition A). During an ion exchange time of 6 hours, Composition A achieved a DOC of 39.4 microns and a CS / E ratio of 13.09, while Compositions 1-4 achieved a similar DOC and a much higher CS / E ratio. Each of Compositions 1-4 achieved a DOC of 39.4 microns or more and a CS / E ratio of 15.15 or more (an increase of about 15.7% or more compared to Composition A). During an ion exchange time of 8 hours, Composition A achieved a DOC of 45.7 microns and a CS / E ratio of 12.85, while Compositions 1-4 achieved a similar DOC and a much higher CS / E ratio. Each of Compositions 1-4 achieved a DOC of 45.9 microns or more and a CS / E ratio of 14.85 or more (an increase of about 15.6% or more compared to Composition A).

[0126] Graph (400) of FIG. 4. FIG. 4 illustrates the compressive stress values ​​for the layer depth values ​​for Compositions 1-4 and Composition A at each ion exchange time in Table 3. The results reported in Table 3 and illustrated in Graph 400 exemplify that the glass composition according to the embodiment described herein can outperform comparable glass compositions in terms of flexibility and strength. The glass composition according to the embodiment described herein can achieve a higher CS / E ratio than similar glass compositions at various ion exchange times. Furthermore, as the ion exchange time and / or DOC increases, the CS / E ratio for the glass composition described herein actually increases, whereas the CS / E ratio for comparable glass compositions may decrease as the ion exchange temperature and time increase.

[0127] A model was used to illustrate a method in which glass compositions according to embodiments described herein, and glass articles made from these compositions, can provide improved mechanical properties for high-strength applications that experience significant bending stress during use, such as flexible cover glass applications. Table 4 below shows the modeled compositions and the Poisson ratio and Young's modulus modeled for each composition. Composition B was modeled as another reference composition. The composition modeled as Composition B was 60.33 mol% SiO2, 19.17 mol% Al2O3, 1.81 mol% MgO, 1.72 mol% CaO, 16.84 mol% Na2O, 0.01 mol% K2O, 0.01 mol% TiO2, 0.09 mol% SnO2, and 0.01 mol% Fe2O3.

[0128]

[0129] The model predicts the bending performance of glass as a function of thickness and plate spacing (referred to as "plate distance (D)") during a bending test. The model takes into account the value obtained by subtracting the bending stress from the existing ion exchange profile (for a given plate spacing) and then calculates the stress intensity for surface defects (e.g., cracks) at any length.

[0130] For example, graph (500) in FIG. 5 shows the modeled bending, ion exchange, and resulting total stress applied to a 75-micron thick glass article composed of composition A during bending at various depths from the surface of the glass article. For graph 500, the modeled peak compressive stress was 800 MPa, the modeled DOC was 15.3 microns, and the modeled plate gap was 9.4 mm. The modeled bending stress applied by the 9.4 mm plate gap is indicated by a solid line in graph 500.

[0131] For the model, the "safe bend" plate spacing is considered when the total stress at the defect depth ("resulting stress profile") is equal to zero so that the bending tensile stress perfectly compensates for the ion exchange-induced compression. As shown in graph (500), for composition A with the modeled stress, "safe bend" occurs at a plate spacing of 9.4 mm when the defect size is 1 micron or less (minimum depth where the stress on the Y-axis is zero). A similar graph was generated for each of the compositions and thicknesses shown in Table 5A below, and the peak compressive stress values ​​reported in Table 5A are in MPa units. The "safe bend" plate spacing distance for a 1 micron defect length for each composition and thickness shown in Table 5A is reported in Table 6. To determine the safe plate spacing reported in Table 6, the modeled bending stress spacing as a function of the modeled plate (solid line in graph 500) was increased until the plate spacing resulted in the "safe bend" plate spacing value for each modeled product. The graph (600) in Fig. 6 illustrates the safe bending plate distance results of Table 6 for glass article thickness. Table 5B reports the modeled maximum center tension values ​​for each modeled product. The maximum CT values ​​reported in Table 5B were approximated as the peak compressive stress and the product of the compression depth divided by the difference between the substrate thickness and twice the compression depth.

[0132] [Table 5A]

[0133]

[0134] [Table 5B]

[0135]

[0136] [Table 6]

[0137]

[0138] As shown in Table 6, the model predicted that compositions 1 to 3 could avoid breakage with a 1-micron defect during bending tests at much smaller plate gaps than composition A. A smaller plate gap implies that the glass compositions can better avoid breakage during bending. At a thickness of 35 microns, glass articles composed of compositions 1-3 were modeled to achieve a safe plate gap of up to 4.44 mm, whereas glass articles composed of composition A were modeled to achieve a safe plate gap of 5.38 mm. At a thickness of 50 microns, glass articles composed of compositions 1-3 were modeled to achieve a safe plate gap of up to 5.88 mm, while glass articles composed of composition A were modeled to achieve a safe plate gap of 7.12 mm. At a thickness of 75 microns, a glass article composed of compositions 1-3 was modeled to achieve a safe plate gap of up to 7.77 mm, while a glass article composed of composition A was modeled to achieve a safe plate gap of 9.39 mm. At a thickness of 100 microns, a glass article composed of compositions 1-3 was modeled to achieve a safe plate gap of up to 9.91 mm, while a glass article composed of composition A was modeled to achieve a safe plate gap of 12.0 mm.

[0139] Although various embodiments have been described herein, they are presented as examples rather than as limitations. Based on the teachings and guidelines set forth herein, it should be evident that adaptations and modifications are intended to be within the meaning and scope of equivalents of the disclosed embodiments. Accordingly, it will be evident to those skilled in the art that various changes in form and detail may be made to the embodiments disclosed herein without departing from the spirit and scope of this description. The elements of the embodiments set forth herein are not necessarily mutually exclusive but may be interchangeable to satisfy various situations, as recognized by those skilled in the art.

[0140] The embodiments of this description are described in detail herein with reference to the embodiments illustrated in the accompanying drawings, and the same reference numerals are used to denote identical or functionally similar elements. References such as "one embodiment," "embodiment," "some embodiments," "in a particular embodiment," etc., indicate that while the described embodiment may include specific features, structures, or characteristics, not all embodiments are required to include specific functions, structures, or characteristics. Furthermore, such phrases do not necessarily refer to the same embodiment. Additionally, when specific features, structures, or characteristics are described in relation to an embodiment, it is considered that those affecting such features, structures, or characteristics in relation to other embodiments are within the scope of knowledge of those skilled in the art, regardless of whether they have been explicitly described.

[0141] The embodiments are exemplary but are not intended to limit the scope of this disclosure. Various other suitable modifications and adaptations of conditions and parameters commonly encountered in the field and obvious to those skilled in the art are within the spirit and scope of this description.

[0142] Indefinite articles used to describe elements or components imply the presence of one or more of these elements or components. Although these articles are typically used to indicate that the noun modified is singular, the articles used herein also include the plural unless otherwise stated in specific cases. Similarly, the definite articles used herein imply that the noun modified may be singular or plural unless otherwise stated in specific cases.

[0143] Directional terms used in this specification—e.g., up, down, right, left, front, back, top, bottom, inside, outside—are made with reference to the illustrated drawings and do not imply absolute directions.

[0144] As used in the claims, "comprising" is an open transition phrase. Since the list of elements following the "comprising" transition phrase is a non-exclusive list, elements other than those specifically mentioned in the list may exist. "Must be composed of" or "must be composed of" as used in the claims limits the composition of the material to a specific material and a material that does not substantially affect the basic and novel properties(s) of the material. "Must be composed of" or "consisting of the whole" as used in the claims limits the composition of the material to the specified material and excludes the unspecified material.

[0145] Unless otherwise noted in specific circumstances, where a range of numerical values ​​including upper and lower limits is cited herein, the range is intended to include its endpoints and all integers and fractions within the range. The scope of the claim is not intended to be limited to the specific values ​​cited when defining the range. Furthermore, when a quantity, concentration, or other value or parameter is given as a range, one or more preferred ranges, or a list of upper and lower preferred values, regardless of whether such pairs are disclosed individually, it should be understood that this specifically discloses any range formed from any pair of any upper range or preferred value and any lower range or preferred value. Finally, where the term "approximately" is used to describe the endpoint of a value or range, the description should be understood to include the specific value or endpoint mentioned. Regardless of whether the numerical value or endpoint of the range cites "approximately," the numerical value or endpoint of the range is intended to include two implementation examples: one modified by "approximately" and the other not modified by "approximately."

[0146] As used herein, the term “about” means that the amount, size, formulation, parameters, and other quantities and characteristics are not precise and do not need to be precise, but include approximations and / or tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art as necessary.

[0147] The terms “substantially,” “substantially,” and variations thereof as used herein are intended to indicate that the described feature is identical or approximately identical to the value or description. For example, a “substantially flat” surface is intended to indicate a surface that is flat or nearly flat. Additionally, “substantially” is intended to indicate that two values ​​are identical or nearly identical. In some embodiments, “substantially” may indicate values ​​within approximately 10% of each other, for example, within approximately 5% of each other, or within approximately 2% of each other.

[0148] The implementation example(s) described above have been explained with the help of functional building blocks that exemplify the implementation of specified functions and their relationships. The boundaries of these functional building blocks are defined arbitrarily here for the convenience of explanation. Alternative boundaries may be defined as long as the specified functions and their relationships are properly performed.

[0149] It should be understood that the phrases or terms used in this specification are for illustrative purposes only and not for limitation. The breadth and scope of this description should not be limited by any of the exemplary embodiments described above, but should be defined by the following claims and their equivalents.

Claims

Claim 1 An ion-exchanged alkali aluminosilicate glass article comprising: 61 mol% to 65 mol% SiO2; 13.5 mol% to 20 mol% Al2O3; 1 mol% to 5 mol% MgO; 0.1 mol% to 2.5 mol% CaO; 15 mol% to 18 mol% Na2O, wherein 20 mol% ≤ Al2O3 mol% + RO mol% ≤ 23 mol%, where RO mol% = MgO mol% + CaO mol%, wherein the glass article is substantially free of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O; and a Young's modulus value measured in GPa before ion exchange; An ion-exchanged alkali aluminosilicate glass article comprising a compressive stress layer extending from the surface of the glass article to a compression depth, wherein the compressive stress layer comprises a peak compressive stress value measured in MPa, and wherein the ratio of the peak compressive stress value to the Young's modulus value is 14 or greater. Claim 2 delete Claim 3 An ion-exchanged alkali aluminosilicate glass article according to claim 1, wherein (Na2O mol% + RO mol% - Al2O3 mol%) ≥ 0 mol%. Claim 4 The ion-exchanged alkali aluminosilicate glass article of claim 1, wherein the glass article comprises a liquidus viscosity in the range of 50 kP to 500 kP measured before ion exchange. Claim 5 An ion-exchanged alkali aluminosilicate glass article according to claim 1, wherein the Young's modulus value is in the range of 70 GPa to 80 GPa. Claim 6 An ion-exchanged alkali aluminosilicate glass article according to claim 1, wherein the peak compressive stress is in the range of 850 MPa to 1400 MPa. Claim 7 An ion-exchanged alkali aluminosilicate glass article according to any one of claims 1 and 3-6, wherein the compression depth is in the range of 5% to 20% of the thickness of the glass article. Claim 8 delete Claim 9 An ion-exchanged alkali aluminosilicate glass article according to any one of claims 1 and 3-6, wherein (MgO mol% / (MgO mol% + CaO mol%)) ≥ 0.

5. Claim 10 An ion-exchanged alkali aluminosilicate glass article according to any one of claims 1 and 3-6, comprising a thickness in the range of 15 microns to 200 microns. Claim 11 An electronic device comprising: an electronic display; and a glass article of any one of claims 1 and 3-6 disposed over the electronic display, wherein the electronic device further comprises a housing comprising a front, a rear and a side and an electrical component at least partially within the housing, the electrical component comprising a controller, a memory and an electronic display, and wherein the electronic display is on the front of the housing or adjacent thereto, and wherein the glass article forms at least a part of the housing. Claim 12 A method for strengthening a glass article, comprising the step of immersing the glass article in an ion exchange solution containing 50 weight% or more of a potassium salt, wherein the glass article comprises: 61 mol% to 65 mol% of SiO2; 13.5 mol% to 20 mol% of Al2O3; 1 mol% to 5 mol% of MgO; 0.1 mol% to 2.5 mol% of CaO; and 15 mol% to 18 mol% of Na2O, wherein 20 mol% ≤ Al2O3 mol% + RO mol% ≤ 23 mol%, wherein RO mol% = MgO mol% + CaO mol%, and wherein the glass article is substantially free of ZnO, SrO, BaO, B2O3, P2O5, Li2O, and K2O; A method for strengthening a glass article, comprising the step of ion-exchanging the glass article in the ion-exchange solution at a temperature in the range of 350°C to 480°C for a period in the range of 1 hour to 24 hours to achieve a compressive stress layer extending from the surface of the glass article to a compression depth and having a peak compressive stress value in the range of 850 MPa to 1400 MPa. Claim 13 A method for reinforcing a glass article according to claim 12, wherein the compression depth is in the range of 5 microns to 40 microns. Claim 14 A method for strengthening a glass article according to claim 12, wherein the period is in the range of 1 hour to 8 hours. Claim 15 A method for strengthening a glass article according to any one of claims 12-14, wherein the glass article has a liquidus viscosity in the range of 50 kP to 500 kP measured before immersion in an ion exchange solution. Claim 16 A method for strengthening a glass article according to any one of claims 12-14, wherein the glass article comprises a Young's modulus value measured in GPa before immersion in an ion exchange solution, wherein the ratio of the peak compressive stress value to the Young's modulus value is 14 or more and 18 or less. Claim 17 delete Claim 18 A method for reinforcing a glass article according to any one of claims 12-14, wherein the glass article comprises a thickness in the range of 15 microns to 200 microns. Claim 19 delete Claim 20 delete Claim 21 delete Claim 22 delete Claim 23 delete Claim 24 delete Claim 25 delete Claim 26 delete Claim 27 delete Claim 28 delete Claim 29 delete Claim 30 delete Claim 31 delete Claim 32 delete Claim 33 delete Claim 34 delete Claim 35 delete Claim 36 delete Claim 37 delete Claim 38 delete Claim 39 delete Claim 40 delete Claim 41 delete Claim 42 delete Claim 43 delete Claim 44 delete Claim 45 delete Claim 46 delete

Citation Information

Patent Citations

  • Method for achieving a stress profile in a glass

    KR1020160089487A

  • Glass composition having high compressive stress after post-ion exchange heat treatment

    KR1020190002671A

  • Glass substrate, chemically strengthened glass substrate and cover glass, and method for manufactruing the same

    US20120052275A1

  • Cover glass and method for producing cover glass

    US20120083401A1

  • Aluminosilicate glasses for ion exchange

    KR1020140131376A